Histopathological findings in lung biopsies with usual interstitial pneumonia: Definition of a new classification score for histological fibrotic stages - Makovická, Mária; Vrbenská, Adela; Makovický, Peter; Durcová, Barbora; Škarda, Jozef; Kamarád, Vojtěch; Miklošová, Mária; Rimárová, Kvetoslava; Michalčová, Patricie; Kráľová, Klaudia; Muri, Jozef (General physiology and biophysics, 2024)
The objective of this article is to describe and classify usual interstitial pneumonia (UIP) changes according to their relevance in the pathology of the idiopathic pulmonary fibrosis (IPF) process. In a cohort of 50 patients (25♀, 25♂) with UIP findings, the percentage ratio between fibrotic and preserved parts of the lungs was quantified. Three quantitative stages of fibrotic involvement of the lung parenchyma and concomitant changes were defined. These are initial (≤20%), advanced (21-40%), and diffuse (≥41%) fibrosis of the lungs. Histologically, temporal heterogeneity is predominant with thickened alveolar septa, interstitial fibrosis, and the presence of fibroblastic foci up to mature diffuse fibrosis with honeycomb changes. The finding is accompanied by variably mature lymphocytic inflammation, presence of macrophages, emphysema, bronchioloectasia of the alveoli, bronchiectasis, bronchial muscle wall hypertrophy, hypertrophy of the vessel walls, alveolar mucosa, focal haemorrhage, and hyalinization of the lungs. Pneumocyte hyperplasia, occasionally atypical in appearance with hobnail changes, as well as squamous metaplasia are observed. In the methodically quantified stages of fibrous involvement, 14 subjects were classified (6♀, 8♂) into the stage of initial fibrosis, 21 subjects (11♀; 10♂) into the stage of advanced fibrosis, and 15 subjects (8♀; 7♂) into the stage of diffuse fibrosis.
Keywords: Hypertrophy; Fibrosis; fibróza; idiopatická plicní fibróza; lidé; plíce; Lung; Biopsy; Idiopathic Pulmonary Fibrosis; hypertrofie; Humans; biopsie